A transcription Factor-sRNA cascade enhances acid tolerance in Lactococcus lactis by rewiring arginine metabolism - Qianqian Song; Pingqiu Jian; Li Li; Qihai Liu; Yadi Yao; Jie Zheng; Bingfeng Tang; Hui Xiong; Yuhui Du; Hui Zhao; Hongji Zhu; Jianjun Qiao; et al. (Food Microbiology, 2026)

Heterogeneous driving mechanisms of urban-rural residential carbon emissions in severe cold agro-pastoral ecotones and differentiated low-carbon development pathways: a case study of inner Mongolia, China - Le Chen; Bingfeng Li; Changxin Liu (Energy and Buildings, 2026)

High-precision dynamic model and life cycle assessment framework reduce decision-making risks for sludge-based carbon mitigation strategies - Feiyi Gao; Shunwen Bai; Xue Zhou; Bingfeng Liu; Huihang Sun; Heng Liang (Environmental Research, 2026)

Mechanism-driven nanostrategies against intracellular infections: Leveraging the host-pathogen interplay - Junheng Zhu; Bingfeng Wu; Meng Luo; Yangqing Peng; Fan Yang; Liu Liu; Zhenming Wang; Dingming Huang (Chemical Engineering Journal, 2026)

Whole Blood Coagulation Detection Based on Thrombus Contraction using Vertical Transmittance Turbidimetry - Yijie Guo; Chenxu Liu; Xin Li; Pengzhu Wei; Bosong Duan; Bingfeng Ju (Journal of Medical and Biological Engineering, 2026)

Fragment-based diffusion modeling and molecular dynamics simulation validation for the discovery of PD-L1 small-molecule inhibitors - Jun Liu; Yuxing Yi; Xiaoyan Wu; Jianhuai Liang; Boping Liu; Bingfeng Wang (Molecular Diversity, 2026)

Global distribution of Synechococcus and its carbon fixation potential in the ocean under climate change - Xinyu Chen; Zhenyan Zhang; Bingfeng Chen; Meng Liu; Yuanchen Chen; Liwei Sun; Josep Penuelas; Haifeng Qian (Limnology and Oceanography, 2026)
Synechococcus , a key genus of marine cyanobacteria, plays a crucial role in global carbon fixation; however, its potential for carbon fixation under future climate change remains underexplored. Here, we utilize machine learning to analyze 689 Synechococcus reference genomes and 953 marine metagenomic samples, uncovering the global distribution of Synechococcus species and their carbon fixation genes. The abundance and carbon fixation potential of Synechococcus in the ocean are primarily driven by carbonate and dissolved oxygen concentrations; however, the highest levels are predominantly found in mid‐latitude and low‐latitude regions, respectively. This contrasting pattern can be attributed to the heterogeneity in carbon fixation potential among different Synechococcus species and their environmental adaptations. Without policy interventions, climate change is projected to decrease Synechococcus abundance by approximately 20% across roughly 25 million km 2 of the surface ocean, primarily in low‐latitude regions. Conversely, the abundance of genes related to carbon fixation in Synechococcus is projected to increase in 50.6% of surface ocean areas. Mitigating greenhouse gas emissions could help preserve current distribution patterns. These findings provide important insights for predicting the carbon fixation capacity and species distribution of marine ecosystems under climate change, along with their potential impacts.

The role of artificial intelligence in advancing population-based cancer registration - Shuai Ding; Mingyuan Liu; Hao Wang; Cheng Song; Luyue Zhao; Zhihao Yang; Yue Wang; Yifan Wang; Haitao Cui; Zihao Liu; Dongrun Liu; Tomohiro Matsuda; et al. (Science Bulletin, 2026)

Glycine and betaine improve the quality of cryopreserved sika deer sperm - Feiyu Peng; Lixiang Liu; Yifeng Yang; Xulin Zhang; Yushi Zhang; Bingfeng Fan; Xiaoyu Chu; Jie Cao; Ying Zhang; Weigang Zhao; Yu Tang; Baozeng Xu (Cryobiology, 2026)

Lysophosphatidic acid-induced YAP activation regulates osteogenesis of MC3T3-E1 - Qin Zhang; Jiayi Liu; Bingfeng Wu; Ying Yuan; Ping Gong; Lin Xiang (Tissue and Cell, 2026)

Theoretical assessment model for resistance of horizontal and vertical mixed progressive collapse of reinforced concrete planar frame including initial damage on the side columns - Bingfeng Liu; Jian Hou; Chuanzhao Xu; Fangchao Lei; Li Song (Engineering Structures, 2026)

Response of Earth surface hazards to underground coal mining revealed by multitemporal UAV photogrammetry - Dongdong Yang; Haijun Qiu; Zijing Liu; Zhuoyang Li; Mohib Ullah; Bingfeng Ye; Guoqing Yang (Bulletin of Engineering Geology and the Environment, 2025)

Different effects of heterocyclic compounds on the diversity and functions of soil microbiota - Wenying Ding; Bingfeng Chen; Minglong Song; Meng Liu; Binghai Lv; Danyan Qiu; Yuke Zhu; Zhenyan Zhang; Mengwei Zhang; Rongshe Zhang; Tao Lu; Haifeng Qian (Journal of Hazardous Materials, 2025)

Particle size-dependent neurotoxicity of microplastics in zebrafish (Danio rerio): Spatially resolved lipidomics links metabolic dysregulation to neurological disorders - Yuexin Li; Guangfeng Kan; Chuanzhou Zhang; Bingfeng Liu; Jie Jiang (Journal of Hazardous Materials, 2025)

The combination of microplastics and glyphosate affects the microbiome of soil inhabitant Enchytraeus crypticus - Huihui Yang; Guogang Zheng; Guoyan Qin; Qi Zhang; Ziyao Zhang; Bingfeng Chen; Chaotang Lei; Meng Liu; Rui Cui; Liwei Sun; Shengjie Xia; W.J.G.M. Peijnenburg; et al. (Journal of Hazardous Materials, 2025)

Enhanced peroxymonosulfate activation by Co/Mn and P modified carbon nitride for ciprofloxacin degradation: Performance, mechanism and toxicity assessment - Bingfeng Lin; Guanghui Liu; Zhijia Zheng; Haiyang Shi; Mengfei Zhang; Xi Yuan; Yingping Huang; Ruiping Li; Cilai Tang (Journal of Environmental Chemical Engineering, 2025)

Superhydrophobic fiber felt integrated with shipborne oil recovery device for all-weather cleanup of viscous oil spills - Yuhan Liu; Bin Li; Yihao Guan; Limei Dong; Bingfeng Li; Wenjun Zhang; Mutai Bao; Yiming Li (Chemical Engineering Journal, 2025)

Catalytic degradation of ethyl acetate at room temperature over Ni/NAC monolithic catalyst - Xiangci Wu; Chenglong Dai; Lisheng Zhang; Ge Gao; Jiahui Shi; Dan Zhao; Bingfeng Fu; Shejiang Liu; Jianfeng Fu; Hui Ding (Journal of Environmental Chemical Engineering, 2025)

Do post-failure landslides become stable? - Haijun Qiu; Yijun Li; Yaru Zhu; Bingfeng Ye; Dongdong Yang; Ya Liu; Yingdong Wei (CATENA, 2025)

Prominent creep characteristics of thermokarst landslides on central Tibetan Plateau under climate warming conditions - Ya Liu; Haijun Qiu; Jiading Wang; Ninglian Wang; Xingyuan Jiang; Bingzhe Tang; Dongdong Yang; Bingfeng Ye; Ulrich Kamp (CATENA, 2024)

Rainfall and water level fluctuations dominated the landslide deformation at Baihetan Reservoir, China - Yaru Zhu; Haijun Qiu; Zijing Liu; Bingfeng Ye; Bingzhe Tang; Yijun Li; Ulrich Kamp (Journal of Hydrology, 2024)

Synthesis, performance evaluation, and plasticization dynamics of biobased vanillic acid plasticizer for poly(vinyl chloride) - Bingfeng Qian; Fang Shen; Huichao Zhu; Jianan Zhang; Mingyuan Wu; Jiuyi Liu; Qingyun Wu; Jianjun Yang (Chemical Engineering Journal, 2024)

Photocatalytic degradation of organophosphorus flame retardants in aqueous solutions: a review and future prospects - Zihui Xu; Lucheng Zhang; Tingting Wang; Mingqing Zhang; Gang Kang; Shilong Wu; Bingfeng Liu (Environmental Science and Pollution Research, 2024)

Comprehensive reutilization of Glycyrrhiza uralensis residue by extrusion-biological pretreatment for coproduction of flavonoids, cellulase, and ethanol - Siyuan Chang; Chenke Yun; Bingqian Yang; Jinao Duan; Tianyi Chen; Lei Liu; Bingfeng Li; Sheng Guo; Sen Zhang (Bioresource Technology, 2024)

Molecular design of hydroxamic acid-based derivatives as urease inhibitors of Helicobacter pylori - Na Wang; Xiaoyan Wu; Jianhuai Liang; Boping Liu; Bingfeng Wang (Molecular Diversity, 2024)

Effects of different assembly strategies on gene annotation in activated sludge - Meng Liu; Nuohan Xu; Bingfeng Chen; Zhenyan Zhang; Xinyu Chen; Yuke Zhu; Wenjie Hong; Tingzhang Wang; Qi Zhang; Yangqing Ye; Tao Lu; Haifeng Qian (Environmental Research, 2024)

Ultra-thin layer HTaMoO6 catalyst for the upgrading of carbohydrates into 5-hydroxymethylfurfural - Lei Zhang; Bingfeng Chen; Ti Zhou; Xiaomeng Cheng; Minghua Dong; Ye Liu; Huizhen Liu; Qingling Xu; Buxing Han (Chemical Engineering Journal, 2024)

Synergistic degradation of Tris (2-Chloroethyl) Phosphate (TCEP) by US/Fenton system: Experimental, DFT calculation and toxicity evaluation - Lucheng Zhang; Tingting Wang; Mingqing Zhang; Qi Liu; Yi She; Shilong Wu; BingFeng Liu (Environmental Science and Pollution Research, 2024)

The bioremediation of the typical persistent organic pollutants (POPs) by microalgae-bacteria consortia: A systematic review - Wenbo Guo; Hongyu Ren; Yinzhu Jin; Zetang Chai; Bingfeng Liu (Chemosphere, 2024)

Efficient activation of peroxymonosulfate by Co/Cu co-substituted-ferrite and carbon composite for rapid degradation of tetracycline in aqueous phase: Performance evaluation and mechanisms - Bingfeng Lin; Cilai Tang; Zhijia Zheng; Mengfei Zhang; Yingping Huang; Xi Yuan; Xiaohong Liu; Yonghong Wu (Chemical Engineering Journal, 2024)

Sequential recovery of protein and ammonium from waste sludge and functional metabolism in a combined process of nutrient recovery electro-fermentation (NREF) - Jiayu Gu; Huihui Zhou; Jing Wang; Kun Feng; Guojun Xie; Bingfeng Liu; Defeng Xing (Resources, Conservation and Recycling, 2024)

Synthesis, characterization and performance evaluation of a nontoxic functional plasticizer for poly(vinyl chloride) derived from sustainable lactic acid - Bingfeng Qian; Panpan Peng; Chenliang Wang; Lijie Wang; Jianan Zhang; Mingyuan Wu; Jiuyi Liu; Qingyun Wu; Jianjun Yang (Journal of Cleaner Production, 2024)

Creep deformation monitoring of landslides in a reservoir area - Bingfeng Ye; Haijun Qiu; Bingzhe Tang; Ya Liu; Zijing Liu; Xingyuan Jiang; Dongdong Yang; Mohib Ullah; Yaru Zhu; Ulrich Kamp (Journal of Hydrology, 2024)

Pollution characteristics and potential health effects of airborne microplastics and culturable microorganisms during urban haze in Harbin, China - Jiahui Jiang; Hongyu Ren; Xiaowei Wang; Bingfeng Liu (Bioresource Technology, 2024)

Effects of polyethylene terephthalate microplastics on cell growth, intracellular products and oxidative stress of Scenedesmus sp. - Jiahui Jiang; Xiaoyu Cai; Hongyu Ren; Guangli Cao; Jia Meng; Defeng Xing; Jes Vollertsen; Bingfeng Liu (Chemosphere, 2024)

Synthesis, characterization and performance evaluation of a flame retardant plasticizer for poly(vinyl chloride) derived from biobased vanillic acid - Bingfeng Qian; Weiyao Wang; Huichao Zhu; Jianan Zhang; Mingyuan Wu; Jiuyi Liu; Qingyun Wu; Jianjun Yang (Chemical Engineering Journal, 2023)

Catalytic degradation of benzene at room temperature over FeN4O2 sites embedded in porous carbon - Hui Ding; Lingxiao Xue; Jiahao Cui; Yongqiang Wang; Dan Zhao; Xing Zhi; Rui Liu; Jianfeng Fu; Shejiang Liu; Bingfeng Fu; Jiahui Shi; Ximeng Xu; et al. (Journal of Hazardous Materials, 2023)

Pyrolysis temperature affects the physiochemical characteristics of lanthanum-modified biochar derived from orange peels: Insights into the mechanisms of tetracycline adsorption by spectroscopic analysis and theoretical calculations - Zhihao Chen; Bingfeng Lin; Yingping Huang; Yanbiao Liu; Yonghong Wu; Rui Qu; Cilai Tang (Science of The Total Environment, 2023)

Metagenomic reveals the methanogenesis metabolic mechanism of high-solids anaerobic digestion of human feces under gradient domestication - Haipeng Wang; Hao Sun; Hongyu Ren; Guangli Cao; Guojun Xie; Defeng Xing; Nanqi Ren; Bingfeng Liu (Chemical Engineering Journal, 2023)

Thermophilic dark fermentation fast start-up of hydrogen production with substrate concentration regulation and moderate pretreatment inoculum - Tianming Yin; Wei Wang; Shengnan Zhuo; Guangli Cao; Hongyu Ren; Jianrui Li; Defeng Xing; Guojun Xie; Bingfeng Liu (Fuel, 2023)

Multi-GNSS precise point positioning (MGPPP) using raw observations - Teng Liu; Yunbin Yuan; Baocheng Zhang; Ningbo Wang; Bingfeng Tan; Yongchang Chen (Journal of Geodesy, 2017)

Chemical composition of fennel essential oil and its impact on Staphylococcus aureus exotoxin production - Jiazhang Qiu; Hongen Li; Hongwei Su; Jing Dong; Mingjing Luo; Jianfeng Wang; Bingfeng Leng; Yanhong Deng; Juxiong Liu; Xuming Deng (World Journal of Microbiology and Biotechnology, 2012)